Synthesis of acrolein by gas-phase dehydration of glycerol over silica supported bronsted acidic ionic liquid catalysts - Munshi, Mudassir K.; Lomate, Samadhan T.; Deshpande, Raj Madhukar; Rane, Vilas H.; Kelkar, Ashutosh A. (Journal of Chemical Technology and Biotechnology, 2010)
BACKGROUND: Glycerol has become readily available as a byproduct from the biodiesel industry. High functionality and relatively low price make it a potential building block to produce value-added derivatives such as acrolein. RESULTS: Dehydration of glycerol to acrolein was performed over several silica supported Bronsted acidic ionic liquids as catalysts. All the catalysts prepared were active for the synthesis of acrolein (conversion of glycerol was observed in the range 35-90% with selectivity to acrolein in the range 29-58%). CONCLUSIONS: Catalyst prepared from triphenyl (3-sulfopropyl) phosphonium 4-methylbenzenesulfonate gave good activity and selectivity at 4 h reaction time. The conversion of glycerol decreased with increase in glycerol concentration. Higher temperature (325 degrees C) resulted in significantly lower conversion as well as selectivity to acrolein. With the use of two additional traps cooled to -7 degrees C, the selectivity to acrolein increased significantly for good catalysts. (C) 2010 Society of Chemical Industry
Keywords: acidic ionic liquids; acrolein; glycerol dehydration; supported catalyst

Synthesis of glycidol from glycerol and dimethyl carbonate using ionic liquid as a catalyst - Gade, Swapna M.; Munshi, Mudassir K.; Chherawalla, Batul M.; Rane, Vilas H.; Kelkar, Ashutosh A. (Catalysis Communications, 2012)
Transesterification of dimethyl carbonate with glycerol has been investigated using various ionic liquids as catalysts. Synthesis of glycidol with high selectivity (78%) has been achieved using tetramethylammonium hydroxide ([TMA][OH]) as a catalyst at 80 degrees C. Effect of various reaction conditions on the activity and selectivity was investigated and catalyst concentration had a significant influence on conversion as well as selectivity to glycidol. Activity as well as selectivity of the catalyst decreased significantly with increase in moisture content. Recycle experiment indicated slight drop in glycerol conversion and selectivity to glycidol because of dilution of reaction mixture and also the presence of products from the initial experiment. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: Glycerol carbonate; Glycidol; Ionic liquid; Transesterification of glycerol